Impact on guidelines: The general practitioner point of view. (August 2020) - Cos, X.; Seidu, S.; Brunton, S.; Harris, S.B.; Jansson, S.P.O.; Mata-Cases, M.; Neijens, A.M.J.; Topsever, P.; Khunti, K.
Abstract: Primary care physicians are uniquely placed to offer holistic, patient-centred care to patients with T2DM. While the recent FDA-mandated cardiovascular outcome trials offer a wealth of data to inform treatment discussions, they have also contributed to increasing complexity in treatment decisions, and in the guidelines that seek to assist in making these decisions. To assist physicians in avoiding treatment inertia, Primary Care Diabetes Europe has formulated a position statement that summarises our current understanding of the available T2DM treatment options in various patient populations. New data from recent outcomes trials is contextualised and summarised for the primary care physician. This consensus paper also proposes a unique and simple tool to stratify patients into 'very high' and 'high' cardiovascular risk categories and outlines treatment recommendations for patients with atherosclerotic cardiovascular disease, heart failure and chronic kidney disease. Special consideration is given to elderly/frail patients and those with obesity. A visual patient assessment tool is provided, and a comprehensive set of prescribing tips is presented for all available classes of glucose-lowering therapies. This position statement will complement the already available, often specialist-focused, T2DM treatment guidelines and provide greater direction in how the wealth of outcome trial data can be applied to everyday practice.